Ginseng adjuvant therapy on COVID-19: A protocol for systematic review and meta-analysis. Issue 43 (29th October 2021) - Shi, Hang; Xia, Yawen; Gu, Renjun; Yu, Shuang
Abstract: Background: Corona virus disease 2019 (COVID-19) is spreading fast and it brings great pressure to the social economy. Many reports revealed that ginseng can develop immunity for respiratory disease, but there is no evidence to prove its effects on COVID-19. This protocol of systematic review and meta-analysis will clarify the safety and effectiveness of ginseng adjuvant therapy on COVID-19 patients. Methods: Different databases (Web of Science, Cochrane Library, PubMed, Chinese Biomedical Literature Database, Chinese National Knowledge Infrastructure, Chinese Scientific Journal Database, Wan fang Database, ClinicalTrials, World Health Organization Trials, and Chinese Clinical Trial Registry) will be retrieved to search related articles according to pre-defined inclusion and exclusion criteria. Clinical recovery time and effective rates will be assessed as the primary outcomes and any changes of patient's condition will be considered as the secondary outcomes. Subgroup analysis and sensitivity analysis will be conducted to explore sources of heterogeneity. Endnote X9.3 will be used to manage data screening. The statistical analysis will be completed by RevMan5.3 and Stata/SE 15.1 software. Results: This study will assess the effects and safety for ginseng adjuvant therapy on COVID-19 patients. Conclusion: The discussion will be considered to determine whether sufficient evidence exists to prove the effects of ginseng adjuvant therapy for COVID-19 patients. Systematic review registration: PROSPERO (ID: CRD42021277843)